From the university classroom to the infant classroom: an experience of teaching with dominos (Journal of Parents and Teachers, 2012)
In this article is explained that students fail maths because they are afraid of the subject. Teachers should make them change their approach towards maths showing them that is possible to lean having fun. The authot proposes a new experience based on dominoes.
Keywords: Experience; Dominoes; learning process; experiencies